Effects of swimming on facial sebum in adolescents. Issue 3 (23rd December 2021) - Morss‐Walton, Peyton C.; Kimball, Ranch; Rosales Santillan, Monica; McGee, Jean S.; Cukras, Anthony; Patwardhan, Sachin V.; Porter, Martina L.; Kimball, Alexa B.
Abstract: Swimmers often complain of dry skin, consistent with decreased skin sebum levels, and yet may also have acne, which is commonly related to elevated sebum levels. Sixteen adolescent swimmers with and without acne were enrolled to examine two markers of facial sebum levels before and after 1 hour of swimming. Swimmers with acne did not have significant decreases in their sebum levels or shine measurements after swimming, whereas swimmers without acne did. Overall, swimming may remove superficial sebum more than follicular sebum and therefore leave swimmers subject to both dry skin and acne simultaneously.